Dynamic power response of microbial fuel cells under external electrical exciting - Wang, Chin Tsan; Chen, Yan Ming; Hu, Zi Yang; Chong, Wen Tong (Elsevier, 2017)
More related studies of microbial fuel cells (MFCs) have been noted recently because of the feature that MFCs could use bacteria to convert organic matter from wastewater into electricity. But facing the slow dynamic response and low power density of MFCs, a technique using external physical exciting with an electrical force, with an intensity ranging from 0 to 8.8 kV/m, was applied in this study to ascertain the bioelectrochemical dynamic response of MFCs. Results show that the rise time of MFCs under external electric impact, regardless of electrical intensity, was shorter than in a case of without electric impacting. Evidence shows that external electric impact gives a significant positive impact on the dynamic performance of MFCs. The dynamic power response of a system under cases of electric impacting is better than in cases of without (i.e., MFCoriginal). In addition, a maximum electric charge of 358.9 × 10−3C in a system whose Oxidation-Reduction Potential (ORP) was −219 mV was obtained in the case of MFCE-4.8 and was 4.07 times that of the MFCoriginal. These findings will be useful to the application of micro-MFCs, especially for those electrically impacting wastewater environments.